Bandwidth Enhancement for circular Microstrip Antenna up to 72% by Drill in the Base of the Microstrip Antenna - et.al, Mahmoud M. Aubais (Al-Qadisiyah Journal of Pure Science, 2017)
A circular microstrip antenna is designed to tone at 2.4 GHz, FDTD method is used to simulate and study of its properties. In this study, the Bandwidth of foam is found 1.67% width dielectric constant 1.07. to broad the Bandwidth we drill two big slots in the base of microstrip, so the Bandwidth increase to 72%, the range of antenna operating was from (1.59 to 3.3 GHz). MATLAB was used to programming. The method applied for other insulators, the results show a increasing in Bandwidth for all cases.